Beyond Bruner’s Constructivism: An Epistemological Synthesis of Discovery Learning in the Qur'an for Holistic Islamic Education - Al Mubarok, Ahmad Furqon; Dimyati, Sanja; Fikri, Muhammad Jauharil; Hernawati, Hernawati; Ghofur, Abdul (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2026)
This study examines the concept of discovery learning in the Qur'an through the perspective of tafsīr tarbawī (educational exegesis). Amid the growing demand for student-centered learning in contemporary education, instructional models that promote active learner participation have become increasingly significant. Employing a qualitative library research approach, this study aims to analyze the manifestation of discovery learning principles in Qur'anic verses, particularly through the narratives of the prophets. The study applies a thematic (mawḍūʿī) interpretation of verses related to the process of seeking knowledge and truth, with a particular focus on the journey of Prophet Ibrahim (Abraham) in Qur'an 6:74–79. The findings reveal that the Qur'an implicitly incorporates learning stages that correspond to the discovery learning model, including stimulation through the observation of natural phenomena (tafakkur), problem identification, data collection, hypothesis testing, and conclusion drawing. The story of Prophet Ibrahim demonstrates the integration of cognitive and spiritual processes in the formation of faith and certainty. This study concludes that the Qur'an functions not only as a source of theological guidance but also as a source of pedagogical inspiration that is highly relevant to the development of contemporary Islamic education. Its educational principles contribute to fostering learners who are critical, reflective, and possess strong moral character. Penelitian ini mengkaji konsep discovery learning dalam Al-Qur’an melalui pendekatan tafsir tarbawi. Di tengah tuntutan pendidikan modern yang menekankan partisipasi aktif peserta didik, model pembelajaran yang berpusat pada siswa menjadi semakin penting. Penelitian kualitatif berbasis studi pustaka ini bertujuan menganalisis manifestasi prinsip-prinsip discovery learning dalam ayat-ayat Al-Qur’an, khususnya melalui kisah para nabi. Metode yang digunakan adalah tafsir tematik (maudhu‘i) terhadap ayat-ayat yang berkaitan dengan proses pencarian pengetahuan dan kebenaran, dengan fokus pada perjalanan Nabi Ibrahim a.s. dalam QS. Al-An‘am [6]: 74–79. Hasil penelitian menunjukkan bahwa Al-Qur’an secara implisit memuat tahapan yang selaras dengan model discovery learning, meliputi stimulasi melalui pengamatan fenomena alam (tafakkur), identifikasi masalah, pengumpulan data, pengujian hipotesis, dan penarikan kesimpulan. Kisah Nabi Ibrahim a.s. memperlihatkan integrasi antara proses kognitif dan spiritual dalam memperoleh keyakinan. Penelitian ini menyimpulkan bahwa Al-Qur’an tidak hanya berfungsi sebagai sumber ajaran teologis, tetapi juga sebagai sumber inspirasi pedagogis yang relevan bagi pengembangan pendidikan Islam kontemporer untuk membentuk peserta didik yang kritis, reflektif, dan berkarakter.